The changing role of ultrasonography examination in patients with rheumatoid arthritis in light of recent studies - Marta Dura (Termedia Publishing House, 2020)
For many years, ultrasonography (US) has been a widely accepted modality used for joint assessment in patients with rheumatoid arthritis (RA). Given the efficacy of present day therapies, there is scepticism whether it is required in the first place. The most recent clinical Targeting synovitis in Early Rheumatoid Arthritis (TaSER) and Clinical Tight Control Therapy (ARCTIC) trials’ results appear to contradict it, yet this does not necessarily mean ultrasound has no place in modern rheumatology. The possibility of detecting inflammation at a subclinical level carries a tremendous predictive value, enabling identification of patients likely to experience an exacerbation in the coming months. Therefore, US should be a part of the decision-making process regarding treatment modification or introduction of any additional interventions, such as glucocorticosteroid injections. The results of the most recent clinical trials do not negate the usefulness of US, but merely suggest that it ought to be used in moderation.